Nutritive value of eight hybrid sorghum grains and three hybrid corns compared in all-concentrate rations Hybrid sorghum and corn characteristics and methods used to nutritionally evaluate them - McCollough, R.L. (Kansas State University. Agricultural Experiment Station, 2011)
In 1971, Kansas produced 234 million bushels of sorghum grain worth $217,000,000, second only to Texas. Most of it is used as an energy source in livestock rations. Since the introduction of hybrid sorghum grain in 1956, yield has increased 25%.
Keywords: Beef; Hybrid sorghum grains; Hybrid corn